Effective Delivery of On-Campus Networked Learning: Reflections on two case-studies - Cook, John; Boyle, Tom (Proceedings of the International Conference on Networked Learning, 2000)
This paper compares the experience of the two studies. In the first study on-line group work was structured around the production of essay-style critiques and the development of prototype multimedia resources. The second study describes an approach to designing on-line interactions between tutors and students that aimed to promote critical debate about an assessment task. The paper then sets down a framework of five key issues that markedly influence the effective delivery of networked collaborative learning in a campus context. The paper concludes by suggesting that if pre-delivery planning of networked learning gives detailed consideration to these issues, then the teaching and learning experience will be greatly enhanced,